(untitled) (Research, Society and Development, 2021)
Considering that the use of items present in the daily lives of students is recognized as an adequate strategy for transmitting and fixing knowledge. In this context, natural dyes can be explored didactically in teaching Chemistry from obtaining to visual characterization. Acid-base natural indicators are dyes extracted from chromophore-rich plant parts. These chromophares are responsible for the variation in color as a function of pH. Among the chromophares, we can highlight anthocyanins, the largest group of natural pigments. The objective of this work is to present some natural dyes with potential for the teaching of Chemistry, aiming at the contribution of the possibilities of alternative materials for teaching in different regional contexts. The data presented demonstrated the diversity of materials, which proved to be efficient in use as an indicator, being excellent natural dyes with easy access and low cost to be used in teaching Chemistry.